Biometria de pirênios, emergência e crescimento radicular das plântulas de Attalea maripa (Aubl.) Mart. - Silva, Auriane da Conceição Dutra da (2016)
The palm Attalea maripa (Aubl.) Mart., occurs naturally in areas of secondary forests, there is the extraction of the pulp and almond oil that has the potential for biofuel production. The aim of this work, conduct study pyrenes of Attalea maripa the biometric aspects of emergence and root growth of seedlings. Inajá fruits were collected from two provenances in the State of Roraima. In Embrapa-RR. Seeds laboratory held cleaning, removal of the pulp and screening. For chapter 1 were conducted three experiments. In the first analyzes were performed morphometric (length, diameter and mass) in 1200 pyrenes, grouped into: small, medium and large. In the second experiment it was taken two replications of 10 seeds each size to determine the water content and water absorption curve. The third experiment was conducted study acceleration of germination, using four replicates of 25 each pyrenes in factorial 2x7, with pyrenes sizes (large and small) and seven pre-germination treatments (scarification, soaking in water for 1 hour, soaking in water for 24 hours, soaking in water for 1h + scarification, soaking in GA3 solution for 1 hour, soaking in GA3 solution for 1h + scarification and control). The seeds were sown in beds containing sand as a substrate in a greenhouse environment. The emergence and development of shoots and roots of the seedlings were evaluated. The second chapter consists of evaluating the morphology and root growth of seedlings of Attalea maripa. Was used structure rhizotron type, containing sand as substrate. It used the decal methodology and measurement of root growth with graduated scale. In the first chapter the results showed that the two lots of pyrenes showed distinct morphological characteristics. Values were observed related to fresh weight of pyrenes from 4,27 g to 9,50 g in lot 1 and 6,28 g to 13,89 g in lot 2 (minimum and maximum values, respectively). Low percentage of emergency was seen in all pre-germination treatments, however the use of gibberellic acid damaged the pyrenes making them unviable for germination. The roots of the seedlings from small pyrenes exhibited greater length. In chapter 2, it was found that the germination of the tubular Attalea maripa is remote hypogeal type and can be further classified as cryptocotyledonary. Viewing the cotyledon petiole was close to 160 days after sowing (DAS), the emergence of shoots on the soil surface occurs at 220 DAS. At the end of the experiment (390 OF) of each seedling was only a main root with a length ranging from up to 46 cm and larger number of lateral roots 1 cm ranged from 3 to 56, depending on the age of the seedlings. So the pyrenes from Cantá and Caracaraí have varying sizes. No effects of pre-germination treatments on seedling emergence. The roots of Attalea maripa in rhizotron conditions present growth perpendicular to the ground, one primary root and variable number of lateral roots.